Dose analysis of InCise 2 multi leaf collimator and IRIS-based stereotactic radiotherapy plans for brain and liver tumors. (12th March 2019) - Ermiş, Ekin; Blatti-Moreno, Marcela; Leiser, Dominic; Cihoric, Nikola; Schmidhalter, Daniel; Henzen, Dominik; Malthaner, Marco; Hemmatazad, Hossein; Tsikkinis, Alexandros; Sermaxhaj, Burim; Aebersold, Daniel M; Herrmann, Evelyn
Abstract: Second-generation multi leaf collimator (MLC) has been introduced for the CyberKnife Robotic Radiosurgery System (Accuray Inc., Sunnyvale, USA) in 2016. The aim of the present study was to compare the plan quality between InCise 2 MLC and IRIS by analyzing dose parameters for small and large targets such as brain metastases and liver tumors, respectively. Ten brain metastases targets and 10 liver targets were selected. The following parameters were analyzed: coverage, dose distributions in planning target volume (PTV) and organs at risk (OAR), conformity index (CI), Nakamura CI (nCI), homogeneity index (HI), gradient index (GI), V12 Gy within brain, treatment time, number of beams, nodes and monitor units (MU). For brain patient group, CI and nCI were lower with IRIS plans (1.18 versus 1.26; p = 0.048 and 1.19 versus 1.28; p = 0.033, respectively), whereas GI values were higher in InCise 2 MLC plans (0.36 versus 0.33; p < 0.01). PTV mean doses were higher with IRIS plans (1.13 versus 1.16; p = 0.03). For liver tumors, InCise 2 MLC plans reached higher GI values (0.32 versus 0.29; p < 0.01). PTV minimum and mean doses were higher with IRIS plans (0.85 versus 0.93; p < 0.01 and 1.17 versus 1.2; p = 0.046, respectively). OAR's mean dose for bowel, left-right kidney and healthy liver tissue were lower with MLC plans (0.02 versus 0.04, 0.02 versus 0.05, 0.07 versus 0.10, and 0.20 versus 0.21; p < 0.01, respectively). Shorter delivery time was reached with InCise 2 MLC for both groups (38 versus 56 min, and 42 versus 56 min; p < 0.01, for brain and liver, respectively). Results of this study showed that second generation MLC plans for intracranial and liver targets were dosimetrically feasible. The main advantages of InCise 2 MLC are the improved dose gradient and delivery time.